ADDRESSING ADOLESCENCE: A CRITICAL ANALYSIS OF LIFE STYLE PROGRAMME IN SCHOOLS IN WEST BENGAL, INDIA - Dey, Amrita (PEOPLE: International Journal of Social Sciences, 2020)
Addressing adolescence through formal school-based sexuality education was part of the United Nations Millennium Development Goals (2000). Life Style educational intervention programme was propagated by West Bengal Board of Secondary Education (from 2004 onwards in the state of West Bengal, India) as a part of this global thrust to cater to the needs of adolescents for improved reproductive health, in combating HIV/AIDS and to ensure their right to access adequate information through school-based sexuality education. Life Style claimed to address adolescents’ issues; physical, psychological, and socio-cultural, in a holistic manner. To implement it, teacher- training was started, a manual for guiding teacher-educators was published and schools allocated compulsorily fixed periods for the dissemination of this programme. This paper focuses on the developmental trajectory of the programme to gain insights into organizational problems; effects of culture on pedagogy and experiences of teacher-educators. The deliberate dissociation of the programme from any reference to sexuality education is also identified and explored as inherent contradictions. The content of the Life Style Teachers’ Manual and the narratives of the associated teacher-educators has been explored and analysed. The qualitative data is specific to a particular time (2010 to 2012) and location (city of Kolkata and Greater Kolkata, West Bengal, India). The sample of respondents has been selected based on purposive sampling. The findings provide suggestive insights into certain social trends and patterns. Explanations of the findings are traced to larger patriarchal social structures and processes. This paper in essence is a qualitative exercise in exploring the conflict and negotiations taking place between established and emerging norms shaping the adolescents’ issues, needs, and rights within the formal educational intervention.